2010
DOI: 10.1590/s0102-76382010000300013
|View full text |Cite
|
Sign up to set email alerts
|

Fechamento primário do pericárdio em cirurgia cardíaca: uma opção segura?

Abstract: Objectives: The primary closure of the pericardium may reduce the risk of cardiac injury during reoperation, especially the right ventricle, aorta and coronary bypass grafts. Nevertheless, concern about adverse hemodynamic effects prevents most heart surgeons of closing the pericardium.Methods: We evaluated 30 patients undergoing open heart surgery consecutively who had the pericardium primarily closed, named (group A) and 18 patients, as a control group (group B) in which the pericardium was left open. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Within this context, Dantas et al32 propose a simple method to facilitate resternotomy during subsequent re-operative procedures. Riedi et al33 determined the strength of respiratory muscle in cardiac surgery and its relationship with the postoperative pulmonary complications but found that preoperative respiratory strength couldn't be a predictor of postoperative pulmonary complication.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, Dantas et al32 propose a simple method to facilitate resternotomy during subsequent re-operative procedures. Riedi et al33 determined the strength of respiratory muscle in cardiac surgery and its relationship with the postoperative pulmonary complications but found that preoperative respiratory strength couldn't be a predictor of postoperative pulmonary complication.…”
Section: Introductionmentioning
confidence: 99%
“…Softer and more flexible drains could help to avoid those lesions. However, it does not solve the issue of contact between drain and heart chambers [4] .…”
Section: Discussionmentioning
confidence: 99%